The use of biofiltration cells to filter contaminated water flowing from a slum settlement in South Africa - Ghanashyam, Aniket (Department of Environmental and Geographical Science, 2020)
Polluted urban surface runoff degrades the receiving water bodies and impacts on downstream water quality and ecological systems. In response, there is growing research attention that is focused on how to treat surface water runoff before it is discharged into these water bodies which includes using a variety of land-based treatment systems. This thesis investigates the performance of large scale, low-cost nature-based filtration systems to clean contaminated water without the addition of chemicals. A relatively small portion of water that is generated and discharged from a slum settlement in South Africa, where water-based services are limited and often dysfunctional, is intercepted and diverted through six biofiltration cells. These cells were packed with different types of natural media, three of which were planted with a variety of reeds while the other cells were kept as control cells. Water that flows into each biofiltration cell is controlled via a network of valves. Flow meters were used to determine the volume and rate of discharge to each cell. The purpose of this study was to determine the effects of HLR (hydraulic loading rate) and HRT (hydraulic retention time) on water quality that was discharged from each cell. This study determined whether the resulting effluent could be repurposed for irrigating edible crops. The final discharge was tested to confirm the differences between the influent and effluent in each cell. Overall the vegetated cell that was packed with large stones (19 - 25 mm aggregates) (LSV) performed the best and displayed reductions of 98.51% of ammonia and 100% of orthophosphate concentrations. E. coli bacteria were also reduced by nearly 100%. Phytoremediation played a role in reducing contamination by removing 97.07%, 89.70% and 100% for ammonia, orthophosphate and E. coli respectively over the study period of four months. Throughout the study, Large Stone Vegetated cells (LSV) reduced nitrite levels by 77.21% with higher removal rates for ammonia, orthophosphate, nitrites, respectively, compared to Large Stone cells (LS). An HRT of approximately seven days resulted in the most improved water quality for LSV, LS, Small Stone (SS) and Small Stone Vegetated cells (SSV) for most of the parameters that were tested. However, orthophosphate leaching occurred in the SSV cell. Peach Pip Vegetated cells (PPV) and Peach Pip cells (PP) did not perform as well as the other cells.